Montmorillonite slurry, clay film, and method for producing montmorillonite slurry
By dispersing lithium-fixed montmorillonite in a water and acetone medium with optional ammonia, and subjecting it to heat treatment, the slurry achieves stable, safe, and efficient production of water-resistant films with fine particle sizes, addressing dispersion and safety issues in existing technologies.
Patent Information
- Application Number
- JP2021119510
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-07-20
AI Technical Summary
Existing methods for preparing lithium-fixed montmorillonite slurries face challenges in achieving stable dispersion and safety, particularly when used for water-resistant films due to the use of organic solvents that may not be suitable for food storage applications, and large particle sizes lead to defects in the formed films.
A method involving the use of a polar medium containing water and acetone, with optional ammonia, to disperse lithium-fixed montmorillonite with a particle size of 15 μm or less, ensuring stable dispersion and avoiding harmful organic solvents, followed by heat treatment to enhance dispersibility.
The resulting slurry achieves fine dispersion of lithium-fixed montmorillonite with excellent stability and safety, enabling the production of films with high water resistance and improved manufacturing efficiency.
Smart Images

Figure 0007601386000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a montmorillonite slurry, a clay film, and a method for producing a montmorillonite slurry. [Background technology]
[0002] Industrial clays are used in a wide range of fields, including as thickeners, binders, rheology modifiers, inorganic binders, civil engineering muds, waterproofing materials, and cosmetic ingredients. Montmorillonite is known as a type of industrial clay. The general crystal structure of montmorillonite consists of a 2:1 layered unit crystal layer in which an alumina octahedral sheet is sandwiched between silicic acid tetrahedral sheets, in which a silicic acid network spreads. In many cases, some of the aluminum atoms in the alumina octahedral sheets, which are the central atoms in the crystalline layers, are replaced by magnesium, which makes the crystalline layers negatively charged, and cations are incorporated between the layers to neutralize the negative charge. In addition, these cations can be exchanged, so montmorillonite exhibits cation exchangeability. The amount of exchangeable cations is called the cation exchange capacity (CEC) and is one of the indicators of montmorillonite's properties.
[0003] It is known that when montmorillonite is subjected to a heat treatment, the interlayer cations (protons, sodium ions, potassium ions, lithium ions, cesium ions, ammonium ions, calcium ions, magnesium ions, etc.) are fixed as a result of dehydration. When the cations are fixed, the basic properties of montmorillonite, such as dispersion stability in water, viscosity, swelling, and cation exchangeability, decrease. In particular, lithium ions are fixed by applying a temperature of about 200°C or higher. Therefore, when montmorillonite containing a certain amount or more of lithium ions between layers is heated to about 200°C or higher, its cation exchangeability is significantly reduced, and even when water is added, it does not return to its original state and its water dispersibility is significantly reduced. It is believed that the fixation of lithium ions by the heat treatment occurs when the lithium ions present between the layers move to vacant sites in the octahedral sheets of the montmorillonite crystal. This phenomenon is called the Hofmann-Klemen effect and is used to control the layer charge density (see, for example, Non-Patent Document 1).
[0004] It has been reported that the functionality of montmorillonite can be enhanced by utilizing the phenomenon of lithium ion fixation by the above-mentioned heat treatment. For example, Patent Documents 1 and 2 describe that a clay film with excellent water resistance (water vapor barrier property) can be obtained by forming a film using an aqueous dispersion of montmorillonite having lithium ions between layers and then subjecting the film to a heat treatment in a dryer. As described above, when montmorillonite having a certain amount or more of lithium ions between layers is subjected to a heat treatment at a specific temperature or higher, its dispersibility in water decreases, making it difficult to form a clay film using the aqueous dispersion (slurry) of the montmorillonite. In fact, the water-resistant clay film described in Patent Documents 1 and 2 is prepared by forming a film using an aqueous dispersion of montmorillonite having lithium ions between layers, and then heating the film to a high temperature in a dryer to fix the lithium ions. However, the methods described in Patent Documents 1 and 2 require a heat treatment after forming a film, so there are limitations to improving the production efficiency. If the water dispersibility (dispersion stability) of lithium-type montmorillonite (lithium-loaded montmorillonite) in which lithium ions are fixed by heating can be improved, it becomes possible to prepare a slurry of the lithium-loaded montmorillonite, and a clay film with excellent water resistance (in this specification, "water resistance" means "water vapor gas barrier property") can be formed simply by applying and drying this slurry. In fact, several techniques for improving the water dispersibility of lithium-loaded montmorillonite have been reported. For example, Patent Document 3 describes that a slurry containing specific amounts of lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and a polar organic solvent having a formamide group has excellent dispersion stability of the lithium-loaded montmorillonite. Patent Document 4 describes that a slurry containing specific amounts of lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and an organic solvent selected from at least acetonitrile and methyl ethyl ketone has excellent dispersion stability of the lithium-loaded montmorillonite. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-247719 A [Patent Document 2] JP 2009-107907 A [Patent Document 3] JP 2015-147300 A [Patent Document 4] JP 2018-83728 A [Non-patent literature]
[0006] [Non-Patent Document 1] "Clay Handbook", Third Edition, Edited by the Clay Science Society of Japan, May 2009, p.125 Summary of the Invention [Problem to be solved by the invention]
[0007] The techniques of Patent Documents 3 and 4 above make it possible to prepare a slurry in which lithium-loaded montmorillonite is stably dispersed, and it is expected that the industrial application field of lithium-loaded montmorillonite as a functional material will expand. However, in these techniques, the safety of the organic solvent, which is essential for making a slurry of lithium-loaded montmorillonite, to living organisms may be a problem. That is, even if no problem occurs in general industrial applications, for example, when a water-resistant film (water vapor gas barrier film) formed using a slurry of lithium-loaded montmorillonite is used as a case or film for food storage, the slurry composition is not necessarily suitable.
[0008] As described in Patent Documents 1 and 2, lithium-loaded montmorillonite is expected to be used as a functional membrane material with excellent water resistance. However, in order to have sufficient functionality as a water-resistant membrane, it is important that the lithium-loaded montmorillonite is dispersed in fine particles in the lithium-loaded montmorillonite slurry. For example, if the particle size of the lithium-loaded montmorillonite dispersed in the slurry is large (if it is aggregated), fine defects are likely to occur in the membrane formed using the slurry, making it difficult to achieve the desired water resistance. Through the study by the present inventors, it has been found that sufficient water resistance can be achieved with a normal membrane thickness (5 to 50 μm) by reducing the particle size (median size, volume basis) of the lithium-loaded montmorillonite dispersed in the slurry to 15 μm or less, and that the smaller the particle size, the higher the water resistance can be achieved even if the water-resistant membrane is made thinner.
[0009] An object of the present invention is to provide a slurry in which lithium-loaded montmorillonite having lithium ions immobilized thereon and reduced cation exchangeability and water dispersibility is stably dispersed, the particle size of the dispersed lithium-loaded montmorillonite being sufficiently small so that safety problems are unlikely to occur in industrial use, a clay film using the slurry, and a method for producing the slurry. [Means for solving the problem]
[0010] The present inventors have conducted extensive research in view of the above problems. As a result, they have found that when preparing an aqueous dispersion of lithium-loaded montmorillonite powder, the lithium-loaded montmorillonite can be stably dispersed in the dispersion medium in a finer state by mixing a specific amount of acetone in the dispersion medium (water) and then mixing this mixture with the lithium-loaded montmorillonite powder, and a slurry with excellent dispersion stability over time can be obtained. The present invention has been completed through further research based on these findings.
[0011] The above object of the present invention has been achieved by the following means. [1] A montmorillonite slurry comprising lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less dispersed in a polar medium containing water and acetone, the lithium-loaded montmorillonite in the dispersed state having a particle size of 15 μm or less. [2] The montmorillonite slurry according to [1], wherein the polar medium does not contain any of a polar organic solvent having a formamide group, acetonitrile, and methyl ethyl ketone. [3] The montmorillonite slurry according to [1] or [2], wherein a proportion of water in the total content of water and acetone in the polar medium is 80 mass% or less. [4] The montmorillonite slurry according to any one of [1] to [3], wherein the polar medium contains ammonia, and the content of the ammonia is 0.1 mmol or more per 1 g of the lithium-loaded montmorillonite in the montmorillonite slurry. [5] The montmorillonite slurry according to any one of [1] to [4], wherein the montmorillonite slurry is subjected to a heat treatment at 30 to 100°C. [6] The montmorillonite slurry according to any one of [1] to [5], wherein the lithium-fixed montmorillonite is obtained by subjecting lithium-type montmorillonite to a heat treatment at 180 to 600°C. [7] A clay film using the montmorillonite slurry according to any one of [1] to [6]. [8] A method for producing a montmorillonite slurry, comprising mixing lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less with a polar medium containing water and acetone to obtain a slurry in which the lithium-loaded montmorillonite is dispersed in the polar medium. [9] The method for producing a montmorillonite slurry according to [8], wherein the polar medium does not contain any of a polar organic solvent having a formamide group, acetonitrile, and methyl ethyl ketone.
[10] The method for producing a montmorillonite slurry according to [8] or [9], wherein a ratio of water to a total amount of the mixed water and the mixed amount of acetone is 80 mass% or less.
[11] The method for producing a montmorillonite slurry according to any one of [8] to
[10] , wherein the polar medium contains ammonia, and the mixed amount of the ammonia is 0.1 mmol or more per 1 g of the lithium-loaded montmorillonite.
[12] The method for producing a montmorillonite slurry according to any one of [8] to
[11] , comprising a step of subjecting a mixture of the lithium-loaded montmorillonite and the polar medium to a heat treatment at 30 to 100°C.
[13] The method for producing a montmorillonite slurry according to any one of [8] to
[12] , wherein the particle size of the lithium-immobilized montmorillonite dispersed in the polar medium is 15 μm or less. Effect of the Invention
[0012] In the montmorillonite slurry of the present invention (hereinafter also simply referred to as "slurry of the present invention"), lithium-fixed montmorillonite having low water dispersibility and a cation exchange ability of not more than a specific level is finely divided and stably dispersed, has excellent dispersion stability over time, and is unlikely to cause safety problems in its industrial use. Furthermore, the clay film of the present invention is a film formed using the slurry of the present invention, and is excellent in water resistance and production efficiency. Furthermore, according to the method for producing a montmorillonite slurry of the present invention (hereinafter also simply referred to as the "slurry production method of the present invention"), it is possible to obtain a slurry in which lithium-immobilized montmorillonite having low water dispersibility, that is, a cation exchange ability of which is below a specific level, is dispersed in a finer, more stably form, has excellent dispersion stability over time, and is unlikely to cause safety problems in industrial use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments except as defined in the present invention.
[0014] [Montmorillonite slurry] The montmorillonite slurry of the present invention is a slurry in which lithium-loaded montmorillonite having a cation exchange capacity of 50 meq (milliequivalent) / 100 g or less is dispersed in a polar medium. This polar medium contains water and acetone, and the lithium-loaded montmorillonite is dispersed in the polar medium in the form of fine particles having a particle size of 15 μm or less. The slurry of the present invention may contain components other than the above-mentioned components within the range that does not impair the effects of the present invention. Each component constituting the montmorillonite slurry of the present invention will be described in detail below.
[0015] <Lithium-fixed montmorillonite> The lithium-fixed montmorillonite used in the present invention has lithium ions (Li +) is fixed by a heat treatment or the like described below. In the slurry of the present invention, the lithium-fixed montmorillonite constitutes the dispersoid. In the present specification, the term "lithium-type montmorillonite" refers to montmorillonite in which the amount of lithium ions (i.e., the amount of leached lithium ions, unit: meq / 100g, the same below) in the amount of leached cations (i.e., the total amount of leached cations, unit: meq / 100g, the same below) is 60% or more, and preferably, the amount of leached lithium ions in the amount of leached cations is 70% or more, more preferably, the amount of leached lithium ions in the amount of leached cations is 80% or more. The amount of leached lithium ions in the amount of leached cations of lithium-type montmorillonite may be 100%, but is usually 99% or less. In addition, in the present specification, the term "lithium-type montmorillonite" refers to montmorillonite whose cation exchange capacity exceeds 50 meq / 100g. The cation exchange capacity of lithium-type montmorillonite is preferably 60 to 150 meq / 100g, more preferably 70 to 120 meq / 100g, and further preferably 80 to 110 meq / 100g.
[0016] In this specification, the "lithium-loaded montmorillonite" has a cation exchange capacity of 50 meq / 100g or less. The cation exchange capacity of the lithium-loaded montmorillonite is preferably 5 to 50 meq / 100g, more preferably 7 to 46 meq / 100g, and further preferably 8 to 40 meq / 100g. In the present invention, the cation exchange capacity of the lithium-loaded montmorillonite means the cation exchange capacity of the lithium-loaded montmorillonite dispersed in a polar medium. In this specification, the "lithium-loaded montmorillonite" refers to a lithium-loaded montmorillonite in which the difference (unit: meq / 100 g) between the amount of leached lithium ions of the lithium-loaded montmorillonite used as a raw material in its preparation (as described above, the lithium-loaded montmorillonite can be obtained by subjecting the lithium-loaded montmorillonite to a heat treatment described below) is preferably 60% or more, more preferably 60 to 99%, and even more preferably 65 to 95% of the cation exchange capacity (unit: meq / 100 g) of the lithium-loaded montmorillonite used as the raw material. The lithium-loaded montmorillonite used in the present invention is preferably in powder form.
[0017] In addition, the lithium-fixed montmorillonite usually contains sodium ions (Na ) as leaching cations in addition to lithium ions. + ), potassium ion (K + ), magnesium ion (Mg 2+ ), calcium ion (Ca 2+ In the lithium-fixed montmorillonite used in the present invention, Na + , K + , Mg 2+ and Ca 2+ The total amount of leached ions is preferably 1 to 30 meq / 100 g, more preferably 1 to 20 meq / 100 g, and even more preferably 1 to 10 meq / 100 g.
[0018] The cation exchange capacity of montmorillonite can be measured by a method based on the Schollenberger method (Clay Handbook, Third Edition, edited by the Clay Science Society of Japan, May 2009, pp. 453-454). More specifically, it can be measured by the method described in the Japan Bentonite Industry Association Standard Test Method JBAS-106-77. The amount of leached cations in montmorillonite can be calculated by leaching the interlayer cations of montmorillonite using 100 mL of 1 M ammonium acetate aqueous solution per 0.5 g of montmorillonite for 4 hours or more, and measuring the concentrations of various cations in the resulting solution using ICP emission spectrometry, atomic absorption spectrometry, etc.
[0019] The lithium-immobilized montmorillonite used in the present invention can be obtained by subjecting lithium-type montmorillonite to a heat treatment to immobilize lithium ions present between layers of the crystal structure. Lithium-type montmorillonite can be obtained, for example, by adding a lithium salt such as lithium hydroxide or lithium chloride to a dispersion of natural sodium-type montmorillonite and carrying out cation exchange. By adjusting the amount of lithium added to the dispersion, the amount of lithium ions in the amount of leached cations in the obtained lithium-type montmorillonite can be appropriately adjusted. Lithium-type montmorillonite can also be obtained by a column method or a batch method using a resin in which a cation exchange resin is ion-exchanged with lithium ions. Lithium-type montmorillonite is also commercially available, for example, Kunipia-M (trade name, manufactured by Kunimine Kogyo Co., Ltd.).
[0020] The lithium-loaded montmorillonite used in the present invention has lower cation exchangeability and water dispersibility than lithium-loaded montmorillonite. This is believed to be because in the lithium-loaded montmorillonite, lithium ions migrate to and are fixed in vacant sites in the octahedral sheets of the clay crystals, electrically neutralizing the clay crystals and creating a tightly closed space between the layers, making it difficult for water molecules to penetrate (making it difficult for hydration of the interlayer cations to occur).
[0021] When preparing lithium-fixed montmorillonite by subjecting lithium-type montmorillonite to a heat treatment, the temperature conditions of the heat treatment are not particularly limited as long as the lithium-type montmorillonite can be made into lithium-fixed montmorillonite. From the viewpoint of efficiently fixing lithium ions and significantly reducing the cation exchange capacity, it is preferable to heat to 150°C or higher. The temperature of the heat treatment is more preferably 150 to 600°C, more preferably 180 to 600°C, more preferably 200 to 500°C, and even more preferably 220 to 400°C. By heating to the above temperature, the cation exchange capacity can be more efficiently reduced and at the same time, the dehydration reaction of the hydroxyl groups in the montmorillonite can be suppressed. The heat treatment is preferably carried out in an open electric furnace. In this case, the relative humidity during heating is 5% or less, and the pressure is normal pressure. The time of the heat treatment is also not particularly limited as long as the lithium-fixed montmorillonite can be made into the above cation exchange capacity, and from the viewpoint of production efficiency, it is preferably 0.5 to 48 hours, more preferably 1 to 24 hours. The moisture content of the lithium-type montmorillonite before the heat treatment is preferably 1 to 12 mass%, and the moisture content of the lithium-fixed montmorillonite after the heat treatment is preferably 0.1 to 5 mass%.
[0022] The content of the lithium-immobilized montmorillonite in the slurry of the present invention is not particularly limited and can be appropriately adjusted depending on the purpose. From the viewpoint of ensuring the fluidity of the slurry and making the kneading and stirring steps practically possible, the content of the lithium-immobilized montmorillonite in the montmorillonite slurry of the present invention is preferably 1 to 30 mass%, more preferably 2 to 25 mass%, even more preferably 2 to 20 mass%, even more preferably 2 to 15 mass%, and also preferably 3 to 12 mass%.
[0023] In the slurry of the present invention, the lithium-fixed montmorillonite is dispersed in a state in which the particle size is 15 μm or less. From the viewpoint of preventing defects in the film formed using the slurry and further improving functionality such as water resistance, the particle size is preferably 12.0 μm or less, more preferably 10.0 μm or less, even more preferably 9.5 μm or less, even more preferably 8.0 μm or less, even more preferably 6.0 μm or less, even more preferably 5.0 μm or less, even more preferably 4.0 μm or less, and particularly preferably 3.0 μm or less. In the slurry of the present invention, the lithium-fixed montmorillonite has no particular lower limit for the particle size, which is usually 1.0 μm or more, may be 1.2 μm or more, may be 1.5 μm or more, or may be 1.8 μm or more. In the present invention, the "particle size" of the lithium-loaded montmorillonite in the slurry is a volume-based median size, which can be determined by a laser diffraction / scattering type particle size distribution measuring device.
[0024] <Acetone> The polar medium constituting the slurry of the present invention includes acetone. The acetone used may be any commonly known and commonly used acetone used as a reagent or industrial product. The content of acetone in the slurry of the present invention is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more per part by mass of lithium-loaded montmorillonite in the slurry. The content of acetone is usually 10 parts by mass or less, and can be 6 parts by mass or less. By setting the content of acetone within the above preferred range, it acts on the lithium-loaded montmorillonite in the presence of water and penetrates between its layers, thereby obtaining a slurry in which the lithium-loaded montmorillonite is stably dispersed in a finer state.
[0025] As a result of the investigations of the present inventors, it has become clear that by using a polar medium containing a mixed liquid of water and acetone, mixing the lithium-loaded montmorillonite with this, and subjecting the polar medium to a heat treatment at 30 to 100°C to cause the lithium-loaded montmorillonite to react with the polar medium, the acetone reacts with the lithium-loaded montmorillonite in the presence of water, and the lithium-loaded montmorillonite in the slurry can be sufficiently finely divided, regardless of whether the polar medium contains ammonia as described below. Furthermore, acetone itself is relatively safe for living organisms and is easily removed by drying treatment, making it highly suitable for use in fields where safety for living organisms is required.
[0026] <Water> The polar medium constituting the slurry of the present invention includes water. There is no particular limitation on the water used, but it is preferable to use water from which ionic components have been removed, such as distilled water or ion-exchanged water. As for the degree of ion removal, the ionic conductivity of the water is preferably 10 μS / m or less, more preferably 5 μS / m or less, and even more preferably 2 μS / m or less. In addition, when the polar medium contains components other than water and acetone, the water derived from the components mixed in the polar medium other than water and acetone also constitutes the water in the slurry. For example, when the polar medium constituting the slurry of the present invention contains ammonia as described below, the water in the ammonia water when ammonia water is used as the ammonia source constitutes the water in the slurry.
[0027] In the polar medium constituting the slurry of the present invention, the proportion of water in the total content of water and acetone is preferably 80 mass% or less, more preferably 75 mass% or less, and may be 70 mass% or less, from the viewpoint of improving the dispersibility of the lithium-fixed montmorillonite. From the same viewpoint, the proportion of water in the total content of water and acetone in the slurry of the present invention is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 20 mass% or more, and even more preferably 25 mass% or more.
[0028] The total content of water and acetone in the polar medium constituting the slurry of the present invention is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and also preferably 95% by mass or more. It is also preferable that the polar medium is entirely composed of water and acetone.
[0029] <Ammonia> The polar medium constituting the slurry of the present invention may further contain ammonia. When the polar medium contains ammonia, a slurry having a small dispersed particle size can be obtained without performing a heat treatment. Even when the polar medium does not contain ammonia, the lithium-immobilized montmorillonite can be micronized by performing a heat treatment. When acetone and ammonia coexist in the slurry of the present invention, a ketimine reaction occurs in which the oxygen atoms of the carbonyl group of acetone are partially replaced by ammonia, and the slurry may be strongly colored yellow to orange. Therefore, when the slurry of the present invention contains ammonia, it is preferable to use it for applications in which coloring is not a problem.
[0030] As the ammonia source, any of aqueous ammonia, gaseous ammonia, and liquid ammonia may be used. When the slurry is produced under atmospheric pressure, however, it is preferable to use aqueous ammonia. When the slurry of the present invention contains ammonia, the content of ammonia in the slurry is preferably 0.1 mmol or more, more preferably 0.2 mmol or more, even more preferably 0.5 mmol or more, and even more preferably 0.8 mmol or more per gram of lithium-loaded montmorillonite in the slurry. By setting the content of ammonia to the above-mentioned preferred value, a sufficient number of molecules of ammonia can penetrate between the layers of the clay crystals of the lithium-loaded montmorillonite, and the solution dispersibility of the lithium-loaded montmorillonite can be further improved. In addition, in consideration of the generation of ammonia odor and production costs, the content of ammonia in the montmorillonite slurry is preferably 10 mmol or less, more preferably 5 mmol or less, even more preferably 4 mmol or less, and even more preferably 2 mmol or less per gram of lithium-loaded montmorillonite in the montmorillonite slurry. In this specification, "per gram of lithium-loaded montmorillonite" specifically means per gram of lithium-loaded montmorillonite blended in the slurry. More specifically, it means per gram of mass of a treated product obtained by extracting the lithium-loaded montmorillonite contained in the slurry from the slurry and treating the extracted montmorillonite at a temperature of 200°C for 24 hours. The heat treatment is preferably carried out in an open electric furnace. In this case, the relative humidity during heating is 5% or less, and the pressure is normal pressure. The amount of ammonia per 1 g of lithium-loaded montmorillonite can be obtained by dividing the amount of ammonia (mmol) in the slurry by the mass of the lithium-loaded montmorillonite in the slurry (i.e., the mass of the treated product obtained by extracting the blended lithium-loaded montmorillonite present in the slurry and heat-treating the extracted montmorillonite at a temperature of 200°C for 24 hours) (unit: g). The ammonia content in the slurry can be measured by the indophenol method, the Kjeldahl method, gas chromatography, or ion chromatography.
[0031] <Other ingredients> The polar medium constituting the slurry of the present invention may contain, in addition to water and acetone, various other components within the range that does not impair the effects of the present invention. In consideration of improving the dispersibility of the lithium-fixed montmorillonite, for example, the polar organic solvent having a formamide group described in JP 2015-147300 A, or acetonitrile or methyl ethyl ketone described in JP 2018-83728 A may be contained. Although it depends on the use of the slurry of the present invention, from the viewpoint of biological safety, for example, it is preferable that the polar medium constituting the slurry of the present invention does not contain any of a polar organic solvent having a formamide group, acetonitrile, and methyl ethyl ketone.
[0032] In addition, the slurry of the present invention may further contain a silane coupling agent, a crosslinking agent, an organic polymer, a non-swelling silicate compound, silica, a surfactant, inorganic nanoparticles, etc., within a range that does not substantially impair the effects of the present invention.
[0033] If the slurry of the present invention has a high clay concentration, it can be diluted to a desired concentration before use.
[0034] [Method for producing montmorillonite slurry] Next, a method for producing the slurry of the present invention will be described. When the polar medium constituting the slurry of the present invention does not contain ammonia, the slurry of the present invention can be obtained by mixing the components (raw materials) constituting the slurry and heat-treating them at 30 to 100° C. That is, by undergoing the above-mentioned heat treatment, acetone in the polar medium acts on the lithium-loaded montmorillonite in the presence of water to penetrate between the layers, thereby obtaining a slurry in which the lithium-loaded montmorillonite is stably dispersed in a finer particle state.
[0035] The method of mixing the raw materials (method of mixing before heat treatment) is not particularly limited, and the raw materials can be mixed simultaneously or in any order. In addition, when mixing, a general bladed agitator, homomixer, universal mixer, planetary centrifugal mixer, Eirich mixer, etc. can be used. Among them, a universal mixer and planetary centrifugal mixer, which can efficiently mix even when the montmorillonite concentration exceeds 20 mass%, can be preferably used. The temperature at which the raw materials are mixed is preferably less than 30°C, and more preferably less than 27°C.
[0036] The heat treatment at 30 to 100° C. after mixing of the above-mentioned raw materials is not particularly limited as long as it is a treatment in which heating is performed at a temperature of 30 to 100° C. From the viewpoints of both dispersibility and handleability of the lithium-fixed montmorillonite, the heat treatment temperature is more preferably 30 to 90° C., more preferably 35 to 90° C., more preferably 40 to 90° C., further preferably 45 to 85° C., and further preferably 50 to 85° C. In addition, this heating temperature may be 80° C. or less, 70° C. or less, and is also preferably 65° C. or less. The time of the heat treatment at 30 to 100°C is not particularly limited as long as the lithium-fixed montmorillonite can be finely divided to a desired particle size, and is appropriately set according to the heating temperature and the like. The heat treatment time is usually 2 hours or more, more preferably 4 hours or more, and even more preferably 6 hours or more. The longer the heat treatment time, the more likely the lithium-fixed montmorillonite can be finely divided. For example, even if the heat treatment temperature is a relatively low temperature of 30 to 50°C, the heat treatment time can be set to 10 hours or more, preferably 15 hours or more, more preferably 20 hours or more, and even more preferably 24 hours or more to more reliably achieve the desired fine particle size of the lithium-fixed montmorillonite. There is no particular upper limit to the heat treatment time, and it is usually 50 hours or less, and sufficient dispersibility can be achieved even if it is 30 hours or less. The heat treatment time tends to be shortened by performing high-temperature and high-pressure treatment using an autoclave or the like. The heat treatment time at 30 to 100° C. is usually 2 to 50 hours, preferably 4 to 40 hours, more preferably 6 to 30 hours, and even more preferably 10 to 30 hours. This heat treatment may be carried out either statically or with stirring.
[0037] In addition, when the polar medium contains ammonia, the slurry of the present invention can be obtained by mixing the components (raw materials) constituting the slurry and subjecting the mixture to the heat treatment, thereby obtaining a slurry having a small dispersed particle size, or can be obtained without subjecting the mixture to the heat treatment. The method of mixing the raw materials is not particularly limited, and the above-mentioned mixing methods can be appropriately applied. The mixing time is also not particularly limited, and can be appropriately set in consideration of the dispersion state of the slurry of the present invention, but mixing is preferably performed for 1 hour or more, more preferably for 2 hours or more, also preferably for 4 hours or more, and also preferably for 10 hours or more. The temperature at which the raw materials are mixed is not particularly limited, and the above heating temperatures can be applied. In addition, from the viewpoint of suppressing coloration due to the ketimine reaction, the temperature is usually preferably less than 30°C, more preferably less than 27°C.
[0038] By the above-mentioned heating treatment or the mixing treatment of mixing with ammonia, the lithium-loaded montmorillonite can be stably dispersed in the dispersion medium as fine particles (dispersoid) having a particle size of 15 μm or less in the slurry of the present invention obtained. The preferred particle size of the lithium-loaded montmorillonite in the slurry is as described above.
[0039] The slurry of the present invention can form a clay film with excellent water resistance simply by forming the slurry on a substrate and drying it to a desired level. In other words, the slurry of the present invention is unlikely to absorb water even when it comes into contact with moisture, and can be suitably used for forming a clay film with high durability. The clay film prepared using the slurry of the present invention can be used, for example, as a packaging film, an electronic substrate, a flame retardant film, a water vapor barrier film, an insulating film, a coated film, and the like. EXAMPLES
[0040] The present invention will be described in more detail below based on examples, but the present invention is not limited to these.
[0041] <Preparation of lithium-fixed montmorillonite> The lithium-type montmorillonite used as the raw material was lithium-type montmorillonite (product name: Kunipia-M, manufactured by Kunimine Industries Co., Ltd.) obtained by ion exchange treatment of natural montmorillonite. 800 g of this lithium-type montmorillonite was placed in an electric furnace (muffle furnace, FO410, manufactured by Yamato Scientific Co., Ltd.) and subjected to heat treatment at 110° C. for 1 hour, and then to heat treatment at 250° C. for 1.5 hours. In this way, a powder of lithium-fixed montmorillonite 1 was obtained. As another sample, 800 g of the lithium-type montmorillonite after the ion exchange treatment was placed in an electric furnace (muffle furnace, FO410, manufactured by Yamato Scientific Co., Ltd.) and subjected to heat treatment at 110° C. for 1 hour and then to heat treatment at 180° C. for 24 hours to obtain a powder of lithium-fixed montmorillonite 2.
[0042] The cation exchange capacity (CEC) of the raw lithium-type montmorillonite and the heat-treated products (lithium-fixed montmorillonite 1 and 2) was measured. The CEC was measured according to the method described in the Japan Bentonite Industry Association Standard Test Method JBAS-106-77. As a result, the CEC of the lithium-type montmorillonite used as the raw material was 105 meq / 100 g, the CEC of the lithium-loaded montmorillonite 1 was 7.7 meq / 100 g, and the CEC of the lithium-loaded montmorillonite 2 was 45.2 meq / 100 g.
[0043] [Preparation of slurry] <Example 1> 45.0 g of distilled water, 10.0 g of lithium-fixed montmorillonite 1, and 45.0 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 40° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, the montmorillonite slurry of Example 1 was obtained.
[0044] <Example 2> 67.1 g of distilled water, 5.0 g of lithium-fixed montmorillonite 1, and 27.9 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 50° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, the montmorillonite slurry of Example 2 was obtained.
[0045] <Example 3> 23.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical Co., Ltd.), 20.0 g of lithium-fixed montmorillonite 1, and 56.0 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.), and then allowed to stand at 25°C for 24 hours without heating to obtain a montmorillonite slurry of Example 3. In the montmorillonite slurry of Example 3, the amount of ammonia blended per 1 g of the lithium-loaded montmorillonite was 0.83 mmol.
[0046] <Example 4> 45.0 g of distilled water, 10.0 g of lithium-fixed montmorillonite 2, and 45.0 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 35° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, the montmorillonite slurry of Example 4 was obtained.
[0047] <Example 5> 24.0 g of distilled water, 20.0 g of lithium-fixed montmorillonite 2, and 56.0 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 50°C for 1 hour at 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 50°C for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, the montmorillonite slurry of Example 5 was obtained.
[0048] <Example 6> 65.5 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical Co., Ltd.), 5.0 g of lithium-fixed montmorillonite 2, and 28.5 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.), and then allowed to stand at 25°C for 24 hours without heating to obtain a montmorillonite slurry of Example 6. In the montmorillonite slurry of Example 6, the amount of ammonia blended per 1 g of the lithium-loaded montmorillonite was 3.30 mmol.
[0049] <Comparative Example 1> 90.0 g of distilled water and 10.0 g of lithium-fixed montmorillonite 1 were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, manufactured by AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, manufactured by KIMBLE Co., Ltd.) and subjected to heat treatment at 80° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, manufactured by Yamato Scientific Co., Ltd.). In this way, a montmorillonite slurry of Comparative Example 1 was obtained.
[0050] <Comparative Example 2> 89.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical Co., Ltd.), and 10.0 g of lithium-fixed montmorillonite 1 were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The resulting mixture was placed in a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 80° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, a montmorillonite slurry of Comparative Example 2 was obtained. In the montmorillonite slurry of Comparative Example 2, the amount of ammonia blended per 1 g of the lithium-immobilized montmorillonite was 1.65 mmol.
[0051] <Comparative Example 3> 90.0 g of distilled water and 10.0 g of lithium-fixed montmorillonite 2 were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, manufactured by AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred into a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, manufactured by KIMBLE Co., Ltd.) and subjected to heat treatment at 50° C. for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, manufactured by Yamato Scientific Co., Ltd.). In this way, a montmorillonite slurry of Comparative Example 3 was obtained.
[0052] <Comparative Example 4> 89.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical Co., Ltd.), and 10.0 g of lithium-fixed montmorillonite 2 were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The entire amount of the resulting mixture was transferred to a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 50°C for 24 hours in a constant temperature and sound oscillating device (product name: DKM400, Yamato Scientific Co., Ltd.). In this way, a montmorillonite slurry of Comparative Example 4 was obtained. In the montmorillonite slurry of Comparative Example 4, the amount of ammonia blended per 1 g of the lithium-immobilized montmorillonite was 1.65 mmol.
[0053] <Comparative Example 5> 44.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical), 10.0 g of lithium-fixed montmorillonite 1, and 45.0 g of ethanol (Kanto Chemical, special grade reagent) were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE) and then allowed to stand at 25°C for 24 hours without heating. In this way, a montmorillonite slurry of Comparative Example 5 was obtained. In the montmorillonite slurry of Comparative Example 5, the amount of ammonia blended per 1 g of the lithium-immobilized montmorillonite was 1.65 mmol.
[0054] <Comparative Example 6> 62.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical), 10.0 g of lithium-fixed montmorillonite 1, and 27.0 g of 2-propanol (IPA, Yamaichi Chemical Industry Co., Ltd.) were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.), and then allowed to stand at 25°C for 24 hours without heating. In this way, a montmorillonite slurry of Comparative Example 6 was obtained. In the montmorillonite slurry of Comparative Example 6, the amount of ammonia blended per 1 g of lithium-immobilized montmorillonite was 1.65 mmol.
[0055] <Comparative Example 7> 44.0 g of distilled water, 1.0 g of 28% ammonia water (Kanto Chemical), 10.0 g of lithium-fixed montmorillonite 1, and 45.0 g of N-methyl-2-pyrrolidinone (NMP, Kanto Chemical) were placed in a beaker and stirred at 25°C for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE). The resulting mixture was placed in a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE) and subjected to heat treatment at 80°C for 24 hours in a constant temperature sound oscilloscope (product name: DKM400, Yamato Scientific). In this way, a montmorillonite slurry of Comparative Example 7 was obtained. In the montmorillonite slurry of Comparative Example 7, the amount of ammonia blended per 1 g of the lithium-immobilized montmorillonite was 1.65 mmol.
[0056] [Test Example 1] Particle size of lithium-fixed montmorillonite (dispersoid) The slurries of Examples 1 to 6 and Comparative Examples 1 to 7 were diluted with water to a solid content of 2 mass%, and the median diameter of the lithium-immobilized montmorillonite was measured by wet particle size measurement. This median diameter is based on volume. A laser diffraction / scattering type particle size distribution analyzer (LA-950V2, manufactured by HORIBA Corporation) was used to measure the median diameter.
[0057] [Test Example 2] Dispersion stability The obtained slurries of Examples 1 to 6 and Comparative Examples 1 to 7 were placed in glass containers and allowed to stand for 24 hours at 25° C. After standing for 24 hours, the dispersion state of the lithium-immobilized montmorillonite was visually observed, and the dispersion stability was evaluated according to the following evaluation criteria. - Evaluation criteria for dispersion stability - ◯: No layer separation occurred and the dispersion was stable. ×: Layer separation occurred and precipitation was observed.
[0058] The results obtained are shown in Table 1 below.
[0059] [Table 1]
[0060] As shown in Table 1 above, when the polar medium was only water, the particle size of the lithium-fixed montmorillonite, which is the dispersoid, could not be made small (15 μm or less) even when the slurry was heated, and the dispersion stability was also poor (Comparative Examples 1 and 3). Furthermore, the above results were not changed even when ammonia was added to the polar medium of Comparative Examples 1 and 3 (Comparative Examples 2 and 4). On the other hand, when the dispersion medium was a combination of water, alcohol, and ammonia, and the slurry was not heated, the dispersion stability of the lithium-loaded montmorillonite, which was the dispersoid, was excellent. However, when the particle size of the lithium-loaded montmorillonite was measured, the particle size was large, and the lithium-loaded montmorillonite was not dispersed with the desired small particle size (Comparative Examples 5 to 6). Furthermore, when a polar organic solvent that is not a lower alcohol (NMP) was used, the particle size of the lithium-fixed montmorillonite, which is the dispersoid, could not be made small as desired, and the dispersion stability was also poor (Comparative Example 7). In contrast, by combining water and acetone as a polar medium and subjecting the slurry to heat treatment, the particle size of the lithium-loaded montmorillonite, which is the dispersoid, can be made small to the desired size, and a slurry with excellent dispersion stability was obtained (Examples 1, 2, 4, and 5). Also, by adding ammonia in addition to water and acetone as a polar medium, the particle size of the lithium-loaded montmorillonite, which is the dispersoid, can be made small to the desired size, even without heat treatment, and a slurry with excellent dispersion stability was obtained (Examples 3 and 6).
Claims
1. A montmorillonite slurry comprising lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less dispersed in a polar medium containing water and acetone, the lithium-loaded montmorillonite in the dispersed state having a particle size of 15 μm or less.
2. The montmorillonite slurry according to claim 1, wherein the polar medium does not contain any of a polar organic solvent having a formamide group, acetonitrile, and methyl ethyl ketone.
3. The montmorillonite slurry according to claim 1 or 2, wherein a ratio of water to a total content of water and acetone in the polar medium is 80 mass% or less.
4. The montmorillonite slurry according to any one of claims 1 to 3, wherein the polar medium contains ammonia, and the content of the ammonia is 0.1 mmol or more per 1 g of the lithium-loaded montmorillonite in the montmorillonite slurry.
5. A clay film using the montmorillonite slurry according to any one of claims 1 to 4.
Citation Information
Patent Citations
Purification method for improving purity of bentonite
CN103213998A
Preparation method of montmorillonite film capable of stably existing in solution
CN112058214A
Clay film and its manufacturing method
JP2008247719A
Synthetic smectite and dispersion liquid containing this, clay film, waterproof film, and method of producing synthetic smectite and waterproof film
JP2009107907A
Montmorillonite slurry, clay film, and method for production of montmorillonite slurry
JP2015147300A
